2012
DOI: 10.1007/s10531-012-0280-8
|View full text |Cite|
|
Sign up to set email alerts
|

Macrofungal diversity in Colombian Amazon forests varies with regions and regimes of disturbance

Abstract: Here we present the results of fungal biodiversity studies from some selected Colombian Amazon forests in relationship to plant biodiversity and successional stages after slash and burn agriculture. Macrofungal diversity was found to differ between forests occurring in two regions (Araracuara vs Amacayacu) as well as between flooded forests and terra firme forests in the Amacayacu region. Macrofungal biodiversity differed between regeneration states of different age in the Araracuara region. Suitable substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 57 publications
2
33
0
Order By: Relevance
“…(Trudell and Edmonds 2004; Christensen and Heilmann-Clausen 2009; López-Quintero et al 2012; O’Hanlon and Harrington 2012; Pradhan et al 2013). Climatic conditions as well as phyto-geomorphologic features affect macrofungal fructification (Brunner et al 1992; Yang et al 2006) and thus the chances of their collection during inventory.…”
Section: Introductionmentioning
confidence: 99%
“…(Trudell and Edmonds 2004; Christensen and Heilmann-Clausen 2009; López-Quintero et al 2012; O’Hanlon and Harrington 2012; Pradhan et al 2013). Climatic conditions as well as phyto-geomorphologic features affect macrofungal fructification (Brunner et al 1992; Yang et al 2006) and thus the chances of their collection during inventory.…”
Section: Introductionmentioning
confidence: 99%
“…The family Dipterocarpaceae was considered restricted to the paleotropics until the latter 20 th century when the monotypic genera Pakaraimaea and Pseudomonotes were described from the Guiana Shield region of South America [18], [19]. Pseudomonotes tropenbosii Londoño, Alvarez & Forero (Dipterocarpaceae subfamily Monotoideae) is known only from southeastern Colombia [19] and was recently shown to be associated with sporocarps of putatively ECM fungi [20]. Pakaraimaea is represented by one species ( P. dipterocarpacea Maguire & P. S. Ashton) with two subspecies ( nitidum and dipterocarpacea ), and forms dense stands of coppicing trees in savanna-fringing forests in the sandstone uplands of Guyana and Venezuela [18], [21].…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers have recently been published on fungal biodiversity in the Colombian Amazon region, reporting new species and new registers. Studies in this region revealed 248 species of macrofungi, but a large number of collections have remained unidentified (López-Quintero et al 2012;Vasco-Palacios and Franco-Molano 2013). Several new taxa of micro-and macrofungi have been published-for instance, new species of Penicillium and Trichoderma López-Quintero et al 2013;VascoPalacios and Franco-Molano 2013;Vasco-Palacios et al 2014).…”
Section: Introductionmentioning
confidence: 99%